Effect of Light Hybrid Halogen Cfl and Filtration Rate on Slow Sand Filter in Lowering Ph and Total Coliform - Muhammad Arus Samudro; Retno Syahriawati Dewi; Aurista Miftahatul Ilmah; Muhammad Aris Ichwanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2024)
PT X is a manufacturing company operating in the steel industry in the Surabaya area. The increasing demand for iron in construction in Indonesia forces companies to add labor to meet production targets. The increase in labor will increase the performance of the company's domestic wastewater plant thereby increasing its value. Total coliform and PH at the company's domestic real waste outlet. This research aims to find out what type of media is good at reducing these 2 parameters. This research uses the methods and slow filter with the flow method down flow and uses 2 types of reactors. The data used is data from company quality test results and quality test results of water samples from the outside of the reactor used. In addition, interviews were also conducted with the company. From the research results, the efficiency of reactor 2 is greater than reactor 1 in reducing PH, namely day 1 with 2.06%: 6.18%, day 6 with 16.49%: 22.68%, and day 12 with 25.77%. % : 28.86%. Meanwhile, the efficiency of reactor 2 is also better in reducing levelstotal coliform with the value for day 1 being 1.58%: 10.10%, day 6 being 37.63%: 48.69%, and day 12 being 70.23%: 84.69%. This research concludes that reactor 2 is more effective in reducing PH levels and total coliform contained in domestic wastewater.